2016
DOI: 10.1111/jdv.13646
|View full text |Cite
|
Sign up to set email alerts
|

Metal allergy in eyelid dermatitis and the evaluation of metal contents in eye shadows

Abstract: Metals were top-rank allergens in patients with eyelid dermatitis as in the remaining patients patch tested. The eye shadow products contained significant amount of nickel, cobalt or chromium to elicit allergic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
0
13
0
5
Order By: Relevance
“…Knowledge of the importance of nickel in cosmetics is less well studied. The safe limit in pigmented makeup products such as eye‐shadows and mascaras has been estimated to be <5 ppm, although discrepant results exist regarding the clinical implications of such exposure …”
Section: Sources Of Nickel Exposurementioning
confidence: 99%
“…Knowledge of the importance of nickel in cosmetics is less well studied. The safe limit in pigmented makeup products such as eye‐shadows and mascaras has been estimated to be <5 ppm, although discrepant results exist regarding the clinical implications of such exposure …”
Section: Sources Of Nickel Exposurementioning
confidence: 99%
“…They are found in pigments that contain other metals. Regardless of its form, exposure to Ni is a frequent cause of contact allergies [16,17]. Cadmium may be an impurity of zinccontaining intermediates, but it could also be added in the production process as a pigment-cadmium sulfide that has an intense yellow color.…”
Section: Introductionmentioning
confidence: 99%
“…A Korean study conducted in 2016 showed that eye shadow and brows contained nickel, cobalt and chromium. [16] Chemical such as titanium dioxide can also cause eye lid edema and dermatitis. [17]…”
Section: Metalsmentioning
confidence: 99%
“…Based on literature report female population are more prone to ocular allergy than male due to over use of cosmetics. [16] Inflammation and irritation Inflammatory conditions induced by eye cosmetics mainly affecting the eyelid, conjunctiva tear film and cornea. It is mainly cause by the chemicals used in the eye cosmetics.…”
Section: Problems Associated With Ocular Cosmetics Allergic Contact Bmentioning
confidence: 99%